Cooking the unpredictable and the impromptu - Luca, Renata De (Clinical Styles. The Journal on the vicissitudes of childhood, 1998)
This article intends to discuss the theoretical statements that direct the work on the psychoanalysis-orientated institutions, like éclairage psychanalytique, unpredictable and impromptu. The starting of these reflections lies on the kitchen work at Bonneuil School.